2012
DOI: 10.1007/s10144-012-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in populations of the yellow‐necked mouse, Apodemus flavicollis, harbouring B chromosomes in different frequencies

Abstract: Two alternative models are used to explain maintenance of polymorphism of B chromosomes (Bs) in populations of a great number of species. The parasitic model suggests deleterious effects of Bs on fitness of carriers, while the heterotic model assumes that, in the absence of drive, equilibrium is produced by beneficial effects of Bs at low numbers. In order to determine the potential contribution of Bs to genetic differentiation and diversity, four populations of Apodemus flavicollis, differing in frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Reported B chromosome prevalence ranged from 11% to 63% in 13 out of 14 populations studied in former Yugoslavia [ 21 , 22 ]. A possible reason for their long-term presence in populations could be their contribution to: genetic variability, adaptive effects and population dynamics [ 22 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported B chromosome prevalence ranged from 11% to 63% in 13 out of 14 populations studied in former Yugoslavia [ 21 , 22 ]. A possible reason for their long-term presence in populations could be their contribution to: genetic variability, adaptive effects and population dynamics [ 22 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, population genetics and dynamics also have an influence on the structure of the parasite fauna of the yellow-necked field mouse (Ferrari, 2005) and possibly explain the differences and similarities found here. In a recent study of yellow-necked field mouse populations in Serbia it was shown that their genetic structure did not reflect geographical distances and predicted barriers (large rivers); rather, it reflected differences in the habitats (Adnadević et al , 2012). In particular, the authors found no statistically significant differences in genetic diversity between two localities separated by the Danube.…”
Section: Discussionmentioning
confidence: 99%
“…Possible adaptive effects of Bs were also postulated by Blagojević et al [ 234 ] upon comparison of head morphology in three populations of this species that have Bs at different frequencies. Adnađević et al [ 235 ], by using amplified fragment length polymorphism (AFLP) markers, made a comparison of populations of A. flavicollis settled in ecologically distinct habitats differing in frequency of Bs, and found that the greatest genetic diversity is in the population settled in optimal conditions for this species featured by the lowest frequency of animals with Bs. The majority of loci that are subject of directional selection, feature either population with lower or with a higher frequency of Bs.…”
Section: Maintenance Of B Chromosomesmentioning
confidence: 99%